Communicating Epistemic Stance: How Speech and Gesture Patterns Reflect Epistemicity and Evidentiality. Issue 3 (2nd April 2016) - Roseano, Paolo; González, Montserrat; Borràs-Comes, Joan; Prieto, Pilar
Abstract : This study investigates how epistemic stance is encoded and perceived in face-to-face communication when language is regarded as comprised by speech and gesture. Two studies were conducted with this goal in mind. The first study consisted of a production task in which participants performed opinion reports. Results showed that speakers communicate epistemic stance both verbally and non-verbally, and that specific prosodic and gestural patterns are used to express different epistemic and evidential meanings. The second study consisted of a rating task in which listeners rated the degree of certainty expressed by the opinion reports. Results showed that the number of gestural high certainty markers used by a speaker was a good predictor of the perception of epistemic high certainty. We thus claim that prosodic and gestural markers can be regarded as overt manifestations of epistemicity and evidentiality, and they appear to be especially effective in the communication of epistemic stance.